Improving sales and operations planning process in a beverage company - Laukkanen, Heta (My University, 2020)
Sales and operations planning (S&OP) is a cross-functional planning process that aims to align different business functions with the corporate strategic plan. The purpose is to balance supply and demand in order to optimize the use of a company’s resources. The process consists of monthly meeting cycles performed by a cross-functional team. The primary goal is to make tactical plans that are supported by planners and management. S&OP has been implemented in many companies already for decades, but the successful management of the process is still causing problems: companies fail to achieve the wanted level of maturity. The problems are mainly due to the process being very people centric. This thesis aims to identify improvement gaps in the S&OP process of a beverage company and give suggestions on how to reach a higher maturity level. The theoretical framework of this thesis thoroughly describes the S&OP process and its implementation as has been presented in previous literature. In addition, a multitude of enablers and barriers are discussed that may affect the successful management of the process. The author also presents a maturity model that helps to identify the current level of the S&OP process at the case company. This thesis was conducted as an assignment to a leading fruit beverage company. Due to the research question that focuses only on the case company’s process, all data was gathered within the company. The data was collected as interviews, observations and self-evaluations. In order to study the process from employees’ point of view interview questions were designed to be open-ended to allow the interviewees to tell freely about the phenomenon. The empirical section compares the research findings with the process design and antecedents presented in the theoretical section. As is common the results imply that in this company the problems are related to the process being people centric. The maturity of the S&OP process in the case company was at a mid-level with most improvements needed in cross-functionality and efficiency if the company wants to reach the next level. The findings showed three main topics that create challenges in the current process. These topics were lack of cross-functional integration, S&OP manager’s important role and lack of efficiency. The results indicate that highlighting the cross-functionality is important for the success of the process as well as careful design. As suggested by previous literature, adding a consensus meeting to the S&OP process of the case company is expected to yield many benefits.
Keywords: S&OP, sales and operations planning